Pengaruh Penggunaan Media Pop Up Book Terhadap Keterampilan Membaca Permulaan Siswa Kelas I UPTD SD Negeri 76 Barru - Sukmawati Sukmawati; Haslinda Haslinda (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to describe the effect of using Pop Up Book media for Class I UPTD SD Negeri 76 Barru. This type of research is pre-experimental research in the form of pretest and posttest design, namely an experiment that only uses one class as the experimental class. Data collection techniques in this study were reading tests and observations. The collected data were analyzed using descriptive data analysis and inferential data analysis. The subjects in this study were 16 students of class I UPTD SD Negeri 76 Barru. The results showed that there was an influence on the use of Pop Up Book media on the beginning reading ability of the first graders of UPTD SD Negeri 76 Barru. This is evidenced by the acquisition of the average student score, namely the average pretest score of 50 before the application of the use of Pop Up Book media, while the posttest average score of students after the application of the use of Pop Up Book media was 72.5. The results of the hypothesis testing carried out obtained tcount = 9.32 and ttable = 3.073. So tcount > ttable or 9.32 ˃ 3, 073, then H0 is rejected, HI is accepted.